Successful subretinal delivery and monitoring of MicroBeads in mice - Fischer, M; Goldmann, T; Wallrapp, C; Mühlfriedel, R; Beck, S; Stern-Schneider, G; Ueffing, M; Wolfrum, U; Seeliger, M (Public Library of Science, 2013)
BACKGROUND: To monitor viability of implanted genetically engineered and microencapsulated human stem cells (MicroBeads) in the mouse eye, and to study the impact of the beads and/or xenogenic cells on retinal integrity. METHODOLOGY/PRINCIPAL FINDINGS: MicroBeads were implanted into the subretinal space of SV126 wild type mice using an ab externo approach. Viability of microencapsulated cells was monitored by noninvasive retinal imaging (Spectralis™ HRA+OCT). Retinal integrity was also assessed with retinal imaging and upon the end of the study by light and electron microscopy. The implanted GFP-marked cells encapsulated in subretinal MicroBeads remained viable over a period of up to 4 months. Retinal integrity and viability appeared unaltered apart from the focal damage due to the surgical implantation, GFAP upregulation, and opsin mistargeting in the immediate surrounding tissue. CONCLUSIONS/SIGNIFICANCE: The accessibility for routine surgery and its immune privileged state make the eye an ideal target for release system implants for therapeutic substances, including neurotrophic and anti-angiogenic compounds or protein based biosimilars. Microencapsulated human stem cells (MicroBeads) promise to overcome limitations inherent with single factor release systems, as they are able to produce physiologic combinations of bioactive compounds.